Respiratory syncytial virus in adults with severe acute respiratory illness in a high HIV prevalence setting. Issue 4 (October 2017) - Moyes, Jocelyn; Walaza, Sibongile; Pretorius, Marthi; Groome, Michelle; von Gottberg, Anne; Wolter, Nicole; Haffejee, Sumayya; Variava, Ebrahim; Cohen, Adam L.; Tempia, Stefano; Kahn, Kathleen; Dawood, Halima; et al.
Summary: Background: There are limited data on the epidemiology of respiratory syncytial virus (RSV) illness in HIV-infected adults or the elderly in Africa. We studied the epidemiology of RSV-associated severe acute respiratory illness (SARI) hospitalizations in adults in South Africa from 2009 through 2013. Methods: Individuals admitted to sentinel surveillance hospitals were investigated by respiratory tract swabs for RSV, using a multiplex real-time polymerase chain reaction assay. The incidence of RSV-associated SARI was calculated for the one site with population denominators. Results: Of 7796 participants investigated, 329 (4%) tested positive for RSV. On multivariable analysis, HIV-infected individuals with RSV-associated SARI had greater odds of being in the age groups 18–44 and 45–64 years (odd ratios (OR) 26.3; 95% confidence interval (CI) 6.2–112.1 and OR 11.4; 95% CI 2.6–50.0) compared with those ≥65 years and being female (OR 2.7; 95% CI 1.4–5.4). The relative risk of hospitalization with RSV-associated SARI was 12–18 times higher in HIV infected individual compared to that of HIV-uninfected. Conclusion: The incidence of RSV-associated SARI was higher in HIV-infected individuals and those aged 65 years and older. Further studies are warranted to describe the disease association of RSV detected in adults with SARI.